(untitled) (Physical Education, Health and Social Sciences, 2025)
It is indeed evident that there is an array of heightened competition among the financial institutions, which calls for strategic emulation of the Human Resource Management (HRM) to establish competitiveness. The purpose of this paper is to determine the mediating effect of human capital development and the commitment level in the relationship between strategic human resource management practices and sustainable competitive advantage in the banking industry. Although much has been written about the concept of strategic human resource management in various businesses, the scholarship on its implementation in the context of financial organizations is still limited. This innovation fills this gap by examining antecedent and mediator influences of strategic HRM on sustainable competitive advantage in banks. In this study, proposition of Strategic HRM practices, human capital development, employee commitment and sustainable competitive advantage are expressed and tested using structural equation modeling (SEM). The research outcomes show that implementation of the opted SHRM practices is significantly related to sustainable competitive advantage since it promotes the human capital and increases the employee commitment levels. Whereby practical pressures and compliance requirements require the banks to have an efficient and comprehensive training, measures for better performance and organizational engagement must also be put in place for the bank to remain competitive.This innovation is important in the financial literature as it supplies details on the strategic function of HRM in finances. The information provided may be of great use to the bank administrators and policymakers to ensure that the HRM is adapted to match the organizational goals to support sustainability and enhance the competitiveness of the business in the long run. Finally, the data point to the need for concurrent professional growth and commitment of the employees as critical success factors in the strategic Human Resource Management in banks.